Absorbed doses from GCR and albedo particles emitted by the lunar surface. (October 2020) - Zaman, Fahad; Townsend, Lawrence W.; de Wet, Wouter C.; Schwadron, Nathan A.; Spence, Harlan E.; Wilson, Jody K.; Jordan, Andrew P.; Smith, Sonya S.; Looper, Mark D.
Abstract: When high energy galactic cosmic ray (GCR) particles collide with the lunar regolith, they eject "albedo" particles from the surface. The albedo particles could be either scattered incident ions, or secondary ions and neutrons produced by the collisions of incident ions with the lunar regolith. In an effort to understand the nature of these albedo particles, we use the MCNP6 transport code to estimate the angular and energy distribution of albedo particles at an altitude of 50 km to calculate the resulting total absorbed dose rates, which are compared with measurements from the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) instrument aboard the Lunar Reconnaissance Orbiter (LRO) spacecraft. MCNP6 simulations estimate that the albedo particles account for 19.9% of the total absorbed dose rate. The albedo photons account for 8.81% of the total absorbed dose rate, the highest among albedo species followed by protons (4.97%), electrons (2.47%), positrons (1.89%), neutrons (1.17%), deuterons (0.5%), tritium ions (0.07%), helium-3 ions (0.02%), and alphas (0.01%). In addition, recent studies indicate the presence of hydrogen on the Moon. We simulate a hypothetical lunar regolith enriched with hydrogen to study its effect on the lunar albedo. The results herein show that the proton absorbed dose rate is slightly increased if hydrogen is present in the regolith, which is primarily caused by the increased flux of energetic albedo protons leaving the lunar surface. Highlights: Understanding the effects of albedo radiation is important for lunar discovery. MCNP6 estimates that albedo particles contribute 20% of the total absorbed dose. Albedo photons account for 9% of the absorbed dose, the highest among albedo species. The estimated dose rates are within 5% of those measured by the CRaTER instrument.